Acute subdural empyema in the young COVID-19 patient- A case report (Bangladesh Journal of Neurosurgery, 2021)
Acute subdural empyema is a surgical emergency. It is life threatening for the patient. It has to be evacuated as soon it is diagnosed. But subdural empyema in a COVID 19 patient is uncommon. Its management put the surgical team to a new dilemma. On one side the patient’s life was at risk and on the other side the whole surgical team might get infected.In this case report, we describe such a case which saved the patient’s life at same time many doctors, nurses and OT attendants became infected.Abbrevaitions: OPD- Out patient department, COVID 19-Corona Virus Disease 2019, NINS- National Institute of Neurosciences, RT-PCR- Reverse transcription polymerase chain reaction. SDE- Subdural empyema, PNS- para nasal sinusesBang. J Neurosurgery 2021; 10(2): 206-209